Decentralisation and Poverty in Developing Countries Exploring the Impact - Jütting, Johannes (OECD Publishing, 2004)
Decentralisation has been advocated by donors and development agencies as an important factor broadening citizen participation and improving local governance, thereby promoting poverty reduction from the bottom up. On the basis of a comprehensive review of 19 country case studies documented in the literature, this paper questions this assumption
Keywords: Development